Crystal structure of Al5O3N3 (15R). (25th January 2017) - Podwórny, Jacek; Pawełek, Alicja; Czechowski, Jerzy
Abstract : Having synthesised an AlON-bonded ceramic corundum material, Al5 O3 N3 (15R) polytype coexisting with α -Al2 O3 was identified. The sample was prepared from an alumina-rich mixture of Al2 O3 and AlN substrates and fired at 1650 °C in a nitrogen atmosphere. Using the X-ray external standard quantitative method, one of the reaction products, α -Al2 O3, was quantified. From the remaining substrates the stoichiometric composition of the second phase was calculated. The applied method of crystal structure determination consisted of three stages. In the first stage, the Le Bail method of X-ray pattern decomposition was used for the extraction of Al5 O3 N3 (15R) diffraction lines from a two-phase diffractogram. The space group and unit-cell dimensions from the isostructural SiAl4 O2 N4 SiAlON phase, producing the same X-ray pattern, were used as input data. Next, the direct structure determination in real space was applied for initial structural model derivation, which was followed by Rietveld refinement. The solved crystal structure of Al5 O3 N3 (15R), except the stacking sequence, proved to be closely related to the structure of Al7 O3 N5 (21R) polytype. The Al5 O3 N3 (15R) is trigonal with space group R -3 m, unit-cell dimensions a 0 = 3.0128 Å, c 0 = 41.8544 Å, and volume V = 329.00 Å 3 . The model of Al5 O3 N3 (15R) polytype structure has positional disordering in one of three (6c) Al sites, which leads to stacking faults in six tetrahedral layers. Every third tetrahedron from LR3 and LR4, LR8 and LR9, LR13 and L R14 layers is rotated by 180°.